PERUBAHAN BATAS USIA MINIMUM PERKAWINAN SEBAGAI UPAYA MENCEGAH DISKRIMINASI GENDER TERHADAP PEREMPUAN - Darania Anisa (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2023)
Gender discrimination can be seen from the number of underage marriages by girls which is influenced by society's stigma against women. Their rights as children are difficult to fulfill like boys. The psychological immaturity of children triggers the occurrence of domestic violence. Global data show that girls who marry before the age of 15 experience a 50% increase in the like chilhood of experiencing domestic violence (KDRT). Every child has the right and the right to protection at an early age and treat equally, without discrimination on the basis of sex. Previously, minimum marriage age for women was 16 (sixteen) years old while men's 19 (nineteen) years of age became 19 (nineteen) due to changes in the regulation on Minimum age of marriage in Law No. 16 of 2019 On marriage as an expression of gender equality as an objective of the Sustainable Development Goals agenda.